Control Techniques for Power Converters with Integrated Circuit - Chen, Wen-Wei (Power Systems,, 2018)
This book offers an overview of power electronic applications in the study of power integrated circuit (IC) design, collecting novel research ideas and insights into fast transient response to prevent the output voltage from dropping significantly at the undershoot. It also discusses techniques and training to save energy and increase load efficiency, as well as fast transient response and high efficiency, which are the most important factors for consumer products that implement power IC. Lastly, the book focuses on power electronics for system loop analysis and optimal compensation design to help users and engineers implement their applications. The book is a valuable resource for university researchers, power IC R&D engineers, application engineers and graduate students in power electronics who wish to learn about the power IC design principles, methods, system behavior, and applications in consumer products.